Krisis Kepercayaan Masyarakat terhadap Lembaga Publik di Era Disinformasi Digital - Hari Suriadi (Suria Academic Press, 2025)
This article explores the decline of public trust in governmental institutions in Indonesia, which has been exacerbated by the widespread dissemination of digital disinformation. False information circulated through platforms such as WhatsApp, Facebook, and TikTok has significantly shaped negative perceptions of institutions like the government, election commissions, and law enforcement agencies. Disinformation campaigns have targeted not only political issues but also health and religion, often resulting in polarization and institutional delegitimization. Using a descriptive qualitative approach and literature review method, this study analyzes the patterns of digital disinformation, its impact on public trust, and the contributing role of low digital literacy. The findings suggest that ineffective public communication by state institutions further deepens the crisis of trust. Therefore, a collaborative strategy involving the state, civil society, and digital platforms is essential to rebuild public confidence through transparent information and the strengthening of critical digital literacy.